Experimental poisoning by Baccharis coridifolia in rabbits - Döbereiner, Jürgen; Rezende, Ana Margarida Langenegger de; Tokarnia, Carlos Hubinger (Pesquisa Agropecuaria Brasileira, 2014)
Baccharis coridifolia DC., a poisonous plant to cattle, was administered by stomach tube to 28 rabbits in order to obtain data not given in the literature, regarding dosage, evolution of poisoning, post-mortem and histopathological findings. Administration of the dried plant material was by means of a separation funnel, which had been adapted to a gastric catheter. The flowering plant, collected in March, was two to four times more toxic to rabbits than when collected at sprouting in November. A dosage of 0.68 g/kg of the flowering plant caused death in 3 out of 6 rabbits and 3.0 g/kg of the plant in its sprouting state caused death in 2 out of 4 rabbits. The doses of 1.36 g/kg of the flowering plant and 4.0 g/kg of the sprouting plant caused death in all 3 and 4 rabbits used. The evolution of poisoning varied from 4 hours to approximately 7 days. Diarrhea was the most common symptom of poisoning and started 3 and a half to 52 hours after administration of the plant. Hemorrhages and edema in the mucosa of the caecum (14 in 19 cases) were the most frequently observed macroscopic lesions. The most constant histopathological alterations were hemorrhages, edema, necrobiosis and necrosis in the lamina propria of the caecum and colon, hemorrhages and edema in the submucosa of the caecum and fatty degenerative perilobular changes in the liver (13/17).